Chemoprotective effects of a recombinant protein from Pyropia yezoensis and synthetic peptide against acetaminophen-induced Chang liver cell death - CHOI, YOUN HEE (Int J Mol Med, 2015)
In the present study, the chemoprotective effects of recombinant Pyropia yezoensis (P. yezoensis) protein 1 (PYP1) were examined in acetaminophen (APAP)-treated Chang liver cells. The analysis of P. yezoensis revealed the presence of both mature and immature variants of PYP1. PYP1s, designated as PYP1 (15 kDa), PYP1-AC (12 kDa) and PYP1-B (5 kDa), were successfully expressed in Escherichia coli, and their chemoprotective effects were then examined. In addition, a peptide of 11 residues (ALEGGKSSGGG), which is a common sequence at the N-terminus all of the PYP1s, was synthesized and examined. The effects of treatment with PYP1s and the synthetic peptide (SP) on cell proliferation were determined by MTS assay. Our results clearly demonstrated that treatment with all the PYP1s and SP significantly promoted the proliferation of Chang liver cells, protecting them against APAP. Thus, we concluded that recombinant PYP1s exert protective effects against injury to Chang liver cells.